(untitled) (Khairulummah, 2024)
This paper examines the rise of the Tehreek-e-Nafaz-e-Shariat-e-Mohammadi (TNSM) as a regional movement advocating for Islamic law in Pakistan’s Malakand Division, its evolution into a significant participant in the Afghan conflict, and its eventual decline. Founded in 1989, TNSM initially focused on implementing Sharia through political and militant means, drawing inspiration from Afghanistan’s jihad against Soviet forces. Its leaders, particularly Sufi Muhammad, sought to replicate the success of the Afghan Mujahideen in Pakistan. Following the US invasion of Afghanistan in 2001, TNSM shifted its focus to support the Taliban’s resistance against US and NATO forces. The organization mobilized extensive local support, raising funds and recruiting thousands of fighters who were dispatched to Afghanistan. Despite these efforts, TNSM’s involvement in the conflict resulted in significant losses of its members and diminishing support in Malakand Division. The movement’s influence waned further after the death of Sufi Muhammad in 2019, leading to its formal decline. This paper provides a comprehensive analysis of TNSM’s rise and fall, its impact on regional dynamics, and its role in the post-9/11 Afghan conflict.